Pneumococcal Endometritis with Peritonitis: Case Report and Review of the Literature - KI Ostrowska; C Rotstein; JH Thornley; LA Mandell (Canadian Journal of Infectious Diseases)
The first case of pneumococcal endometritis with peritonitis in a woman using tampons is described. The patient responded to removal of the tampon and administration of broad spectrum antibiotics. The pathogenesis of pneumococcal endometritis and peritonitis and the potential significance of a tampon in situ are discussed.